The Israeli Blockade on Gaza: Its Effects and Future - Al-Zaeem, Ibrahim Saqir; Mohd Nor, Mohd Roslan; Lokman, Ainul Asyraf (Journal Al-Muqaddimah, 2024)
After Hamas had won the legislative elections with vast majority in January 2006, the Israeli occupation, along with Arab and international parties, imposed a severe blockade on the Gaza Strip which affected all life aspects there. 15 years since, this study presents the causes, effects, future, and attempts to end the blockade. The researcher uses the historical approach and addresses two topics: The blockade and its effects, and attempts to end the blockade and Gaza future. Then the study ends with several results. Mainly, the Israeli blockade was imposed to overthrow Hamas and paralyze its military power, the American and European position is in favor of the Israeli occupation while the Arabs remain silent and carry out the will of the Israelis and Americans, and the blockade led to a humanitarian crisis that affected the Palestinians at social, psychological and health levels.